Employment risk and optimal trade policies - Eun Kwan Choi; Jiong Chen (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
This paper considers trade policies and welfare in a Harris-Todaro model with risk averse workers. Workers are assumed to have identical and homothetic preferences, but their incomes differ, depending on whether and where they are employed. When workers are equally weighted, maximizing social utility is equivalent to maximizing the utility of a rural worker. An optimal policy consists of a production subsidy on the exportable and an import tariff. This model explains the widespread use of import tariffs of manufactured goods along with production subsidies on the export sectors in some LDCs.
Keywords: F13; 330; Employment Risk; Trade Policies; Außenwirtschaftspolitik; Arbeitsmarkttheorie; Risiko; Dualökonomie; Stadtflucht; Theorie